Organ donation and transplantation within the Zulu culture - B.R. Bhengu; H.H.M. Uys (AOSIS, 2004)
Greater knowledge and technological advancement in the field of transplantation has increased the demand for organ donation beyond the supply of organs, especially among the black communities. This imbalance arises from the few sources of organs, limitations on the techniques of organ retrieval, disparities in the allocation of organs and socio-cultural factors. The aim of this study was to investigate the extent to which Zulu cultural norms and social structures influence an individual's decision to donate an organ or to undergo transplantation. A qualitative approach using an ethno-nursing method was selected. Semi-structured interviews were conducted with a transplant co-ordinator representing the professional sector, with traditional healers and religious leaders representing the folk sector, and with the general public representing the popular sector of the health care system. Both urban and rural settings were used. Conclusions arrived at showed that knowledge was lacking among Zulu speaking people about organ donation and transplantation and misconceptions about the topic were related to Zulu life patterns, beliefs about death, burial and life hereafter, and values and social structures. Recommendations with regard to the promotion of organ donation and transplantation among Zulu speaking people were made based on culture-sensitive and culture-congruent principles.